506-P: Branched-Chain Amino Acids Promote Occurrence and Development of Cardiovascular Disease Dependent on Triglyceride Metabolism via Activation of the mTOR/SREBP-1/Betatrophin Pathway - ZHANG, JIE; HU, WEN (Diabetes (New York, N.Y.), 2024)
Background: Branched-chain amino acids (BCAAs) has been associated with the development of cardiovascular disease (CVD). However, the underlying mechanism remains uncertain. Methods: The clinical study included 1302 subjects guided by diet and exercise intervention for 4 years and subsequent follow-up. We established a hyperbranched-chain aminoacidemia rat model induced by high fructose diet (HFTD). Additionally, we investigated the relationship between BCAAs and TG level and its regulatory mechanism in vitro. Results: As baseline BCAA percentile increased, subjects were more likely to have a higher prevalence and incidence of diabetes, non-alcoholic fatty liver disease, and CVD risk. Both individual BCAAs and total BCAAs were independently associated with subsequent CVD risk. HFTD led to insulin resistance (IR) and higher levels of BCAAs in the rat model. Further investigation indicated that HFTD led to IR via the IRS-1/Akt/GSK-3β pathway and betatrophin expression was increased. Metformin significantly reversed the above effects. In vitro, we found BCAAs increased TG levels by regulating the mTOR/SREBP-1/betatrophin signaling pathway. Conclusions: BCAAs promote occurrence and development of cardiovascular disease dependent on TG metabolism via activation of the mTOR/SREBP-1/betatrophin pathway.